Geological setting of the Southwestern Boa Vista Aquifer, State of Roraima, Brazil, from shallow vertical electric sounding - Souza, Lena Simone Barata; Carvalho, Franklin Williams Silva de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Twenty vertical electrical sounding profiles were executed during the dry season in the Paricana campus of the Federal University of Roraima. Three geoelectrical units were identified: (a) the lower resistivity unit with values ρa< 1,000 Ω.m attributed to mudstone layers; (b) the middle resistivity unit with values 1,000 Ω.m < ρa < 20,000 Ω.m attributed to sandstone layers; and (c) higher resistivity unit with values ρa > 50,000 Ω.m attributed to lateritic ferruginous concretions and/or ferruginous sandstones. From these three units, seven geoeletrictal patterns can be seen. Patterns 1 and 3 (located in the SW and WNW of the study area) configure the best permoporosity zone in the area because the pore-bearing lateritic concretions are neighboured by paleolakes and actual seasonal lakes. In addition, these patterns 1 and 3 display an extremely sand-grained character. Patterns 2, 4 and 6 (NW, mid-eastern, N and NE) present moderate permoporosity because clay-bearing materials are interpreted as reaching to 10 m depth. Patterns 5 and 7 are attributed to a predominance of clay-bearing material in such a way that it acts as a sealant material to the aquifer protecting it from contamination from the surface.